Pengaruh Kompetensi Kepemimpinan, Budaya Organisasi Terhadap Kinerja Aparatur Sipil Negara Pada Dinas Kesehatan Kabupaten Aceh Tengah - Nuswantoro, Patriandi; Harun, Tirmiara (Biram Samtani Sains, 2023)
Initial observations obtained with the State Civil Apparatus in carrying out its duties and responsibilities have not been as expected. Most of the State Civil Apparatus yet able to carry out and complete the task well, there is even a tendency for the State Civil Apparatus irresponsible shown with apathy to the problems. Methods of data collection is done through a questionnaire distributed to State Health Department of Civil Administrative Central Aceh. Samples taken as many as 107 respondents. The data obtained were then processed using SPSS. This analysis includes test reliability, validity, regression, statistical test through the test t-test, Ftest and determinant coefficient (R2) and classical assumption. The test results showed that the t-test and Leadership Competencies, Cultural Organization positive and significant effect on the performance of the State Civil Apparatus. The test results R2 is 0.620 explain that relationship is quite strong and positive between the independent variable on the dependent variable, by 62% while the remaining 28% are influenced by other variables outside of this study.